2019
DOI: 10.3390/ijerph16162949
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Modeling Approach for Water Management in a River–Reservoir System

Abstract: A coupled model is an effective tool to understand the nutrient fate associated with hydrodynamic and ecosystem processes and thereby developing a water resource management strategy. This paper presents a coupled modeling approach that consists of a watershed model and a hydrodynamic model to evaluate the nutrient fate in a river–reservoir system. The results obtained from the model showed a good agreement with field observations. The results revealed that the Shuikou reservoir (Fuzhou, China)exhibited complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The overall spatial structure analysis indicated that an ∼62% variability for CEC contaminants was contributed by the downstream sites S1–S3. These results are consistent with the findings of Zhang et al, who reported that the downstream sites were more polluted with poor water quality owing mainly to the restricted movement of water closer to the Shuikou Reservoir . It was further argued that the restrictions in the water flow may cause advection and diffusion to induce changes in pollutant loads .…”
Section: Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall spatial structure analysis indicated that an ∼62% variability for CEC contaminants was contributed by the downstream sites S1–S3. These results are consistent with the findings of Zhang et al, who reported that the downstream sites were more polluted with poor water quality owing mainly to the restricted movement of water closer to the Shuikou Reservoir . It was further argued that the restrictions in the water flow may cause advection and diffusion to induce changes in pollutant loads .…”
Section: Results and Discussionsupporting
confidence: 92%
“…These results are consistent with the findings of Zhang et al, who reported that the downstream sites were more polluted with poor water quality owing mainly to the restricted movement of water closer to the Shuikou Reservoir . It was further argued that the restrictions in the water flow may cause advection and diffusion to induce changes in pollutant loads . Several years ago, Huang et al also argued that the construction of dams and reservoirs led to changes in water exchange capacity and dilution, which in turn resulted in greatly deteriorated water quality …”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With an area of 60,992 km 2 , the MRW (25 C and 1617 mm, respectively, and approximately 70% of the precipitation occurs between April and September [27,28]. Based on official population records, the populations in 2010, 2015, and 2020 were 10.75, 11.02, and 11.72 million, respectively.…”
Section: Study Areamentioning
confidence: 99%
“…To create a linkage model, a watershed model is the boundary condition for the hydrodynamic and water quality model of a three-dimensional numerical model, and internal and external linkages are necessary [14]. Several studies have examined the linkage between watershed and reservoir models using the hydrological simulation program-Fortran (HSPF) model [15] and the environmental fluid dynamics code (EFDC) model [16], which has been used to simulate the watershed runoff and reservoir water quality of a river estuary [14] or a river-reservoir combined system [17]. The HSPF-EFDC linkage model has also been used to enhance the prediction accuracy of water quality in rivers using the ensemble Kalman filter (EnKF) technique [18,19].…”
Section: Introductionmentioning
confidence: 99%